2018
DOI: 10.25103/jestr.111.05
|View full text |Cite
|
Sign up to set email alerts
|

CFD Simulation Analysis of Building Density on Residential Wind Environment

Abstract: With the rapid urbanization and expansion of construction demands in China, the continuously increasing density of residential buildings has led to outdoor pedestrian discomfort in residential wind environment. To analyze the relationship between residential building density and wind environment, simulation cases of residential buildings with different building densities were presented in this study. First, the wind environment characteristics of residential districts with different building densities were est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…However, these studies have mainly focused on urban morphology, mesoscale layout, and microscopic details of buildings. On the basis of CFD simulation of the wind environment in residential districts, Hu Kaihua et al [8] analyzed the quantitative relationship between building density and wind environment. They indicated that building density has a negative linear relationship with the average outdoor wind speed ratio (WSR) in residential districts, but it shows a positive linear relationship with the average air age.…”
Section: State Of the Artmentioning
confidence: 99%
“…However, these studies have mainly focused on urban morphology, mesoscale layout, and microscopic details of buildings. On the basis of CFD simulation of the wind environment in residential districts, Hu Kaihua et al [8] analyzed the quantitative relationship between building density and wind environment. They indicated that building density has a negative linear relationship with the average outdoor wind speed ratio (WSR) in residential districts, but it shows a positive linear relationship with the average air age.…”
Section: State Of the Artmentioning
confidence: 99%
“…The results showed that the wind speed ratios of open spaces and lane entrances are higher than those of other places [49]. The simulation results of Hu et al indicated that when the residential BD increases from 0.18 to 0.32, the mean wind speed ratio of the residential area decreases by 0.18 [50]. Guo et al considered that there was a negative correlation between ventilation efficiency and BD in Dalian City, and proposed measures such as using ventilation channels and increasing building height to improve urban ventilation performance [18].…”
Section: Discussionmentioning
confidence: 96%
“…Hadavi and Pasdarshahri quantified the effects of the wind velocity, urban planning district density, and urban form on the infiltration rate via CFD simulations, and concluded that building tightness enhancement could reduce the infiltration rate and augment the exfiltration rate [20]. Hu et al analyzed the relationship between the residential building density and wind environment and reported that when the residential building density increases from 0.18 to 0.32, the outdoor average wind velocity ratio decreases by 0.18 and the average air age increases by 58.63 s [21]. Hong and Lin compared the wind environments of several residential areas with different layout patterns and tree arrangements and concluded that orienting the long facades of buildings parallel to the prevailing wind direction can yield satisfactory thermal comfort [22].…”
Section: Introductionmentioning
confidence: 99%